Impact of Bacterial Phenotypic Variation with Bacteriophage therapy: A Pilot Study with Prosthetic Joint Infection Isolates. (June 2022) - Doub, James B.; Urish, Ken; Lee, Martin; Fackler, Joseph
Highlights: Phage therapy is a promising adjuvant therapeutic in treating prosthetic joint infections The activity of phages can differ between in vivo S. aureus clinical isolates Phenotypic variations of phage attachment receptors likely cause differing activity When discordant activity occurs, retreatment may be needed for reproducible outcomes Abstract: Background: : Given the specificity of bacteriophage attachment receptors, a single bacterial isolate is currently utilized to match to a bacteriophage therapeutic, thereby extrapolating activity to all bacteria in vivo. Consistently, the main bacteriophage attachment receptor for Staphylococcus aureus is teichoic acid, and it is known that this receptor has phenotypic variations in different in vivo environments. Consequently, the aim of this study was to determine whether bacteriophage activity is similar across all in vivo prosthetic joint infection environments. Methods: : Three patients with prosthetic joint infections who had S. aureus grow from arthrocentesis cultures and at least three deep tissue cultures were analyzed for growth inhibition with a library of 56 bacteriophages. Results: : Discordant bacteriophage activity was seen across the different in vivo environments. Furthermore, bacteriophages with the most robust lytic potential to the arthrocentesis isolates usually did not demonstrate activity corresponding to all the deep tissue clinical isolates. Conclusion: : Variations of bacteriophage activity can occur between the different in vivo clinical environments, which is likely secondary to different glycosylation patterns of teichoic acid. Consequently, if discordant activity is present, retreating with bacteriophages that have activity is likely needed for effective, reproducible outcomes.